(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
In the digital era, the younger generation needs to develop digital literacy to maintain physical and mental health when interacting with the digital world. This community service activity was attended by 55 respondents who were Madrasah students at the Jamiatul Qurro Palembang Islamic Boarding School in the form of a short education about the CERDIK principle for students using power points followed by initial health screening anthropometric index )The average age is 14.96 years, and the majority are male (54.55%). The average body mass index was 20.78 ± 4.07, which was normal and tended to be higher in women 21.04 ± 4.56. The average systolic blood pressure was 113.91 ± 9.75 mmHg, diastolic pressure 75.73 ± 7.35. From the respondents’ anthropometric measurements, it was found that the average waist circumference was 71.67 ± 9.71, hip circumference 81.9 ± 12.95, arm circumference 24.81 ± 3.97, and neck circumference 31.48 ± 3.91. The average waist, arm, and neck circumference tend to be higher in men, while the average hip circumference tends to be higher in women. — Di era digital, penting bagi generasi muda untuk mengembangkan literasi digital agar mereka tetap menjaga kesehatan fisik dan mental saat berinteraksi dengan dunia digital. Top of FormKegiatan pengabdian kepada masyarakat ini diikuti oleh 55 responden yang merupakan siswa MA Pondok Pesantren Jamiatul Qurro Palembang berupa edukasi singkat mengenai upaya hidup CERDIK bagi para siswa dengan menggunakan power point yang dilanjutkan dengan skrining awal kesehatan, indeks antropometri (. Rata-rata usia 14,96 tahun dan mayoritas berjenis kelamin laki-laki (54,55%). Rata-rata indeks massa tubuh 20,78 ± 4,07 yang terkategori sebagai normal (IMT antara 18.5-24,9) dengan kecenderungan lebih tinggi pada perempuan 21,04 ± 4,56. Rata-rata tekanan darah sistolik 113,91 ± 9,75 mmHg, tekanan diastolik 75,73 ± 7,35. Dari pengukuran antropometri responden didapatkan rata-rata lingkar pinggang 71,67 ± 9,71, lingkar panggul 81,9 ± 12,95, lingkar lengan 24,81 ± 3,97, dan lingkar leher 31,48 ± 3,91. Rata-rata lingkar pinggang, lingkar lengan dan lingkar leher cenderung lebih tinggi pada laki-laki, sedangkan rata-rata lingkar panggul cenderung lebih tinggi pada perempuan.